DE-based Robust Feedback Controller for Longitudinal Cruise Control of Helicopter - Solihin, Mahmud Iwan; Legowo, Ari; Akmeliawati, Rini; Budiyono, Agus (2011)
This paper presents a robust state feedback controller tuning via constrained optimization using DE (differential evolution). The controller gain is optimized based on linear state-space model of the plant such that the closed-loop system achieves maximum stability radius. The desired control performance is specified by assigning closed-loop poles region which is handled as a constraint in the optimization. The proposed controller design technique is applied to a longitudinal cruise control of a small scale helicopter. The control of small-scale helicopter is a MIMO problem which increases the complexity of the controller design task. The simulation result is shown to evaluate the effectiveness of the proposed controller design technique. Comparison with that of conventional LQR-based controller is also presented.